Immunoglobulin G4‐positive interstitial pneumonia associated with pleuroparenchymal fibroelastosis. Issue 4 (8th March 2022) - Sugino, Keishi; Ono, Hirotaka; Saito, Mikako; Igarashi, Seiji; Kurosaki, Atsuko; Tsuboi, Eiyasu
Abstract: A 79‐year‐old former smoking Japanese man was admitted to our hospital with a 2‐year history of dry cough and dyspnoea on exertion. High‐resolution computed tomography of the chest revealed reticulation and perilobular opacity with bronchial wall thickening and ground‐glass opacities (GGOs) in both lungs, in addition to subpleural dense consolidation (pleuroparenchymal fibroelastosis‐like lesion; PPFE‐like lesion) predominantly in the bilateral upper lobes. Serum immunoglobulin G4 (IgG4) was elevated (348 mg/dl). Lung biopsy specimens obtained by video‐assisted surgery revealed a mixture of usual interstitial pneumonia (IP) and non‐specific IP pattern admixed with PPFE. In addition, immunohistochemical staining of IgG4 showed numerous IgG4‐positive plasma cells. Consequently, he was diagnosed with IgG4‐positive IP associated with PPFE. We initiated a combination therapy with prednisolone and cyclosporine as a calcineurin inhibitor. During prednisolone tapering, his clinical conditions and GGOs improved gradually over 12 months. However, reticular opacities and PPFE‐like lesions remained unchanged, and pulmonary function test findings slightly deteriorated. Abstract : We describe a case of immunoglobulin G4‐positive interstitial pneumonia associated with pleuroparenchymal fibroelastosis, confirmed by video‐assisted thoracoscopic surgery. Combination therapy with prednisolone and cyclosporine showed long‐term efficacy and safety.